Diffusion Characteristics of Human Plasminogen(as Shown by Two Agar Diffusion Techniques) - Stuckey, R. J; Wolf, P (Thrombosis and Haemostasis, 1969)
The relative diffusion rates of human plasminogen in agar has been compared with immune rabbit γ globulin and with streptokinase. A ratio of 1.1106 was found for plasminogen/immune rabbit γ globulin diffusion and a ratio of 0.80 for plasminogen/ streptokinase. These values were unaltered when plasminogen in normal fresh plasma and serum was replaced by three differently prepared plasminogen concentrates. Taking the D20 value for rabbit γ globulin as 4.23 × 10–7 cm2 sec−1 and for streptokinase the value of 6.1 × 10–7 cm2 sec–1, the corresponding values for human plasminogen were 4.7 and 4.9 × 10–7 cm2 sec–1. The widely divergent D20 values for human plasminogen and plasmin in the literature are reviewed and discussed.